Developing A Mobile Cartoon Structural Model to Enhance Critical Thinking Among Economics' Undergraduates - Yin, Khoo Yin; Ahmad, Noor Aini; Ismail, Ramlee (International Journal of Psychosocial Rehabilitation, 2020)
Economics students are facing problem to think critically and participate effectively in the collaborative learning context. Developing mobile cartoons that are related to students’ daily life and address aspects of thinking can help improve students’ critical thinking. The aim of this study is to develop a structural model for promoting economics students’ critical thinking. This new model is based on Vygotsky’s (1997) Zone of Proximal Development (ZPD) theory and Multimedia Learning Theory (Mayer, 2014). This study employed the quantitative research method. Phase one involved the developing of the model. In phase two, survey design was employed. A total of 293 economics students from two public universities were selected as samples. The findings from the Exploratory Factor Analysis retained six factors; which were conceptual understanding, analyse the problem, analytical, decision making, creativity and organize. Confirmatory Factor Analysis was employed and indicated good fit to the model. This study employed SEM to validate a structural model for Mobile Cartoons and this model can be used for future research. The findings from this study may assist lecturers and students to promote critical thinking. Future mobile cartoons research could focus on developing the application to enhance critical thinking with a larger sample.